Probiotic application for sustainable aquaculture - Mahmoud A.O. Dawood; Shunsuke Koshio; Mohamed M. Abdel-Daim; Hien Van Doan (Wiley Publishing Asia Pty Ltd, 2025)
Aquaculture, which constitutes one of the largest food production sectors in the world, is preferably practiced with natural organic products rather than with synthetic chemicals or antibiotics. In addition to the daunting challenge of providing food and livelihood to the exponentially increasing world population, the aquaculture industry is key to ensuring that development is based on environmentally sustainable practices, specifically in the production of aquafeeds. Terrestrial microorganisms that act as natural defence systems of cultured species have been identified as the main producer for the beneficial bacterial candidates. Probiotics have recently gained popularity as beneficial microbes candidates in cultured organisms to maintain the health condition and well-being of different aquatic animals. This review aimed to understand the necessity of using probiotics as a sustainable alternative to regulate the growth performance, feed utilisation and general health condition for sustainable aquaculture. Also, explanatory discussion about the host microbiota and its ability to produce different probiotic strains and the probiotic functionality to ameliorate the host immunity to provide the interactive effects on the host-derived probiotics. By presenting the results obtained from the previous studies about the ability of probiotics to sustain the aquatic animal’s performances, this study condensed the current knowledge and information for future research and development of the probiotic application in aquaculture.